Functional β-cyclodextrins as the active centres on the silica surface for toxic ions sorption - Belyakova, L.A.; Lyashenko, D.Yu.; Shvets, A.N. (Украинский химический журнал, 2013)
Nanoporous β-cyclodextrin-bonded silica, which differ by functional substituents of the wide edge of attached cyclic oligosaccharide molecules, were synthesized. The structure and chemical composition of the surface of nanoporous organosilicas were found. Sorption of mercury (II), cadmium (II), and zinc (II) from dilute acidic nitrate solutions by nanoporous organosilicas was studied. Sorption results were analyzed using Lagergren’s kinetic model and Langmuir and Freundlich models for equilibrium adsorption. The interpretation of interaction features of mercury, cadmium and zinc nitrates with β-cyclodextrin-bonded silica was done according to the theory of hard and soft acids and bases. Синтезовано нанопористі β-циклодекстринвмісні кремнеземи, які відрізняються функціональними замісниками широкого краю закріплених молекул циклічних олігосахаридів. Встановлено структуру та хімічний склад поверхні нанопористих органокремнеземів. Вивчено сорбцію ртуті (II), кадмію (II) та цинку (II) з розведених кислих нітратних розчинів нанопористими органокремнеземами. Результати сорбції проаналізовано з використанням кінетичної моделі Лагергрена та моделей рівноважної адсорбції Ленгмюра і Фрейндліха. Особливості взаємодії нітратів ртуті, кадмію та цинку з циклодекстринвмісними кремнеземами інтерпретовані з позицій теорії твердих і м’яких кислот та основ. Синтезированы нанопористые β-циклодекстринсодержащие кремнеземы, отличающиеся функциональными заместителями широкого края химически привитых молекул циклических олигосахаридов. Установлена структура и химический состав поверхности нанопористых органокремнеземов. Изучена сорбция ртути (II), кадмия (II) и цинка (II) из разбавленных кислых нитратных растворов нанопористыми органокремнеземами. Результаты сорбции проанализированы с использованием кинетической модели Лагергрена и моделей равновесной адсорбции Ленгмюра и Фрейндлиха. Особенности взаимодействия нитратов ртути, кадмия и цинка с циклодекстринсодержащими кремнеземами интерпретированы с позиций теории твердых и мягких кислот и оснований.